Inflammation and clinical presentation in neurodegenerative disease: a volatile relationship - Bettcher, Brianne Magouirk (2012)
A proposed immune mechanism that potentially modifies or exacerbates neurodegenerative disease presentation in older adults has received considerable attention in the past decade, with recent studies demonstrating a strong link between pro-inflammatory markers and neurodegeneration. The overarching aim of the following review is to synthesize recent research that supports a possible relationship between inflammation and clinical features of neurodegenerative diseases, including risk of development, cognitive and clinical correlates, and progression of the specified diseases. Specific emphasis is placed on providing a temporal context for the association between inflammation and neurodegeneration.